Assisting Communities to Build a Sustainable Future – A Report on Sustainable Jersey - Prabhakar Sangolli, Nakul (Tufts Archival Research Center, 2023)
Smaller government units are better at meeting the specific needs of their communities and adapting solutions to local conditions. Many cities in the US are investing in sustainability departments and becoming global leaders in sustainability. However, most local governments have limited resources to address emerging problems, and when higher levels of government fail to act, the responsibility often falls on local actors. This report captures the efforts of state-local sustainability programs in setting standards, offering guidance, and coordinating resources to encourage local steps toward sustainable transformation.; Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy.; Submitted to the Fletcher School of Law and Diplomacy.; Advisor: Barbara Kates-Garnick.